Impact of non-performing assets on profitability in Nepalese Commercial Banks (Patan Pragya, 2020)
The degree of non-performing assets (NPAs) best demonstrates the adequacy of the financial part of a nation. The amount of non-performing assets affects not only the banking industry but also the total financial system and the economy of the country. The motivation behind this investigation is a push to evaluate the effect of Non Performing Assets on the profitability of Nepalese commercial banks. The study cover the period 2013 July 16 to 2018 July 16. Further, the examination is made to investigate the impact of various gatherings of banks. In particular, Government owned bank and private area banks on the financial business in such manner. Five out of twenty four individual private division banks and one out of three, government claimed banks have been considered with the end goal of the investigation for as sample. The investigation depends on optional information gathered from the Nepal Rastra Bank's site just as yearly report of concern banks. To beat the examination objective clear measurements are utilized to portray the essential highlights of the information in the investigation, and inferential insights have been utilized to get to the effect of non-performing assets on profitability of the banks. Besides, credit deposit ratio, employee expenses over all out operating expenses and gross non-performing assets have been taken in to thought as free factor and Return on assets and earnings per share are a piece of ward variable. The appraisal of private part banks uncovers that the development pace of NPAs is low when contrasted with the administration claimed Agriculture Development Bank. The administration claimed bank has neglected to deal with the issue of unsecured loan adequately because of which the development in such loans has been marvelously high. Besides, the effect of NPA on profitability has been done as positive in relationship.